2014
DOI: 10.1007/s00276-014-1313-7
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of the anterior communicating artery complex: gender relationship

Abstract: PurposeThe anatomy of the anterior communicating artery complex plays a critical role in surgical treatment of anterior cerebral circulation aneurysms. A thorough description of vascular variations of the anterior communicating artery complex seems to be lacking. The aim of this study was to describe the anatomical variations of the anterior communicating artery complex.MethodsThe study group consisted of 411 subjects (52.31 % women), without any intracranial pathologies, that had undergone head computed tomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 27 publications
3
18
0
1
Order By: Relevance
“…In the literature, the frequency of normal vascularity was found to be 52.55% (n:411) in a study including only normal subjects. (3). There is also another study with data reporting that normal ACA-AcomA variation was seen in 63.3% (n:128) of patients with cerebral aneurysm (4).…”
Section: Discussionmentioning
confidence: 93%
“…In the literature, the frequency of normal vascularity was found to be 52.55% (n:411) in a study including only normal subjects. (3). There is also another study with data reporting that normal ACA-AcomA variation was seen in 63.3% (n:128) of patients with cerebral aneurysm (4).…”
Section: Discussionmentioning
confidence: 93%
“…2e), which was found in 5 Krzyzewski et al, 2015 patients (1.76 %) and the triple ACA found in 11 (3.88 %) (Fig. 2f).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found a significant difference in the prevalence of anatomical variants of the cerebral arterial circle among different ethnic groups (De Silva et al, 2009;KlimekPiotrowska et al). The prevailing anatomical variant in most studies has been the typical form of the anterior cerebral artery-anterior communicating artery complex with a range between 14.2-76.25 %.…”
Section: Discussionmentioning
confidence: 99%
“…The anterior communicating artery (ACoA) connects the two anterior cerebral arteries, dividing them into pre-communicating (A1) and postcommunicating (A2) segments. ACoA, A1, A2 segments, and the recurrent artery of Heubner are collectively known as the AcoA complex [1]. Anatomical variations in this complex are common and are detected in 58-85% of all patients with ACoA aneurysms [2].…”
Section: Introductionmentioning
confidence: 99%
“…A range of different arterial variations was indexed, including fenestration, duplication, trifurcation, hypoplasia, and aplasia [3]. Several efforts have been made to classify the ACoA complex variations as they may influence the surgical approach of any coexisting vascular disease [1].…”
Section: Introductionmentioning
confidence: 99%